SYSTEMATIC LITERATURE REVIEW TERHADAP DESAIN PILE CAP PADA BANGUNAN BERTINGKAT BERDASARKAN KOMBINASI BEBAN - Alifiah Hafizah (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2026)
Construction of multi-storey buildings in Indonesia has grown rapidly, increasing the structural complexity of foundation systems, particularly the pile cap, which distributes axial, lateral, and combined loads from the upper structure to the pile group. Previous studies mostly examined pile cap behaviour through single aspects, such as soil bearing capacity or conventional design methods, while integration of combined load scenarios remains underexplored. This study aims to systematically map the development of pile cap design research for multi-storey buildings based on load combinations. Its novelty lies in combining a Systematic Literature Review (SLR) following the PRISMA protocol with bibliometric analysis using VOSviewer and RStudio (bibliometrix), producing both qualitative synthesis and quantitative visualization of research trends, keyword networks, and collaboration patterns not jointly examined in prior pile cap literature. The method involved a two-stage search in the Scopus database covering 2021–2025, screening 1,326 articles down to 47 final articles for analysis. Results show structural analysis, seismic response, and pile foundations remain dominant themes, while numerical methods such as the Strut-and-Tie Model and Finite Element Method increasingly replace conventional approaches. The journal Buildings emerged as the most productive source, with a notable increase after 2023. Integration of combined loading conditions with pile cap design remains a significant research gap requiring further investigation.